10‐1: Invited Paper: OLED Lifetime Improvement with Exciplex Sensitized Triplet‐Triplet Annihilation. Issue 1 (May 2017) - Lin, Bo-Yen; Tseng, Po-Chen; Lee, Ming-Zer; Hsiao, Yi-Ze; Chiu, Tien-Lung; Lin, Chi-Feng; Hsieh, Julie; Chen, Stanley; Lee, Jiun-Haw
Abstract : A new emission mechanism was proposed to enhance the OLED operation lifetime by using exciplex emission to sensitize the triplet‐triplet annihilation blue emission. 3‐times improvement in operation lifetime was achieved due to the alleviation of electron accumulation at the interface of the hole‐transporting layer and the emitting layer.